1999
DOI: 10.1086/301031
|View full text |Cite
|
Sign up to set email alerts
|

[ITAL]HUBBLE SPACE TELESCOPE[/ITAL] Observations of Galactic Globular Cluster Cores. II. NGC 6273 and the Problem of Horizontal-Branch Gaps

Abstract: We present observations of the center of the Galactic globular cluster NGC 6273, obtained with the Hubble Space T elescope Wide Field Planetary Camera 2 as part of the snapshot program GO-7470. A BV color-magnitude diagram (CMD) for D28,000 stars is presented and discussed. The most prominent feature of the CMD, identiÐed for the Ðrst time in this paper, is the extended horizontal-branch blue tail (EBT) with a clear double-peaked distribution and a signiÐcant gap. The EBT of NGC 6273 is compared with the EBTs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
96
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 29 publications
(73 reference statements)
10
96
0
Order By: Relevance
“…Besides u Cen and NGC 2808, the only other globular cluster reported to have a signiÐcant EHB population fainter than mag is NGC 6273 (Piotto et al 1999). M V \ 4.5 Thus, Ñash-mixed stars probably do not comprise a signiÐ-cant fraction of the hot HB stars in classical EHB globular clusters such as NGC 6752 or M13, in which nearly all the EHB stars have mag.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides u Cen and NGC 2808, the only other globular cluster reported to have a signiÐcant EHB population fainter than mag is NGC 6273 (Piotto et al 1999). M V \ 4.5 Thus, Ñash-mixed stars probably do not comprise a signiÐ-cant fraction of the hot HB stars in classical EHB globular clusters such as NGC 6752 or M13, in which nearly all the EHB stars have mag.…”
Section: Discussionmentioning
confidence: 99%
“…Other globular clusters with long blue HB tails, e.g., M13, M80 and NGC 6752, do not contain a sufficient number of the faintest EHB stars mag) to deter-(M V Z 4.5 mine if an EHB gap is present (see, e.g., Fig. 7 of Piotto et al 1999). Thus, NGC 2808 stands out as the globular cluster in which an EHB gap is most easily detected observationally.…”
Section: Ehb Gapmentioning
confidence: 99%
See 2 more Smart Citations
“…(1999) and Bono etal. (2001) have discussed the red giant branch (RGB) bump, and compared the predicted position and dimension of this feature with the observed ones; have used the star counts on the HB and on the RGB to gather information on the helium content and on the dependence of the helium content on the cluster metallicity; Zoccali & Piotto (2000) have made the most extensive comparison so far available between the model evolutionary times away from the main sequence and the actual star counts on the subgiant branch (SGB) and RGB; Cassisi et al (2001) have compared the observed and theoretical properties of the asymptotic giant branches; Piotto et al (2000) have used the color-magnitude diagrams in this database to study the Galactic globular cluster relative ages, and Piotto et al (1999b) have started to investigate the Galactic globular cluster blue straggler (BS) population, and have shown how the BS color-magnitude diagram and luminosity function can differ in clusters with rather different morphologies.…”
Section: Large Sets Of Photometric Measurementsmentioning
confidence: 99%